Opportunities for Intercultural Environment Creation in Ukrainian Agrarian University - Bilotserkovets, Marina; Fomenko, Tetiana; Lushchyk, Yuliia (Educational Challenges, 2024)
This study aims to highlight the significance of creating intercultural competence among students in Ukrainian higher education institutions (HEIs), especially in the context of European integration. The goal is to investigate the potential impact of Euro Union (EU) educational policies and the Association Agreement between Ukraine and the EU on students’ intercultural competence, and to offer recommendations for the effective implementation of intercultural education. The methodology covers a comprehensive set of theoretical and empirical research methods, including the analysis of scientific sources, regulatory documents, an online questionnaire, pedagogical observation, and direct interviews with Humanities instructors. The research specifically focuses on 160 first and second-year master’s students in the specialties of “Agroengineering” and “Electricity, electrical engineering, and electromechanics” at Sumy National Agrarian University, taking the course “Communications in the International Environment” during the academic year 2023-2024. The results of the study provide a perspective on the attitudes of students toward international harmony, equality, and social values. The findings reveal that the students prioritize living without war and conflict, national security, and national greatness. However, the study also shows that there are challenges to developing intercultural skills, as students express less interest in an active social life, improving the welfare of those in need, and making decisions that affect their community. The pedagogical observation and expert evaluations underline the need for specialized training to enhance intercultural skills among engineering students. The conclusion is that the study’s dual focus on national specificity and international relevance offers actionable perspectives for educators, policymakers, and researchers. It promotes a deeper understanding of the constraints and opportunities in intercultural competence development to meet the demands of a globalized world. At a national level, the study highlights the specific challenges faced by master students in Ukrainian HEIs and the necessity for specialized training to enhance intercultural communication skills. Internationally, the research aligns with EU educational policies and Council of Europe initiatives, contributing to the broader discourse on intercultural competence in higher education. Recommendations include the incorporation of interactive teaching methods, fostering intercultural dialogue, and promoting a nuanced understanding of intercultural communication.